Korelasi Dana Pihak Ketiga, Capital Adequacy Ratio, Non Performing Financing Terhadap Pembiayaan Pada PT. Bank Muamalat Indonesia - Fauli Majdi, Zulha; Rafiqi, Iqbal; Faizah, Maftuhatul; Mujibno; Supriyadi (Jurnal Perbankan Syariah, 2025)
This study aims to analyze the relationship between third party funds, capital adequacy ratio, non-performing financing partially and simultaneously on financing at PT. Bank Muamalat Indonesia. The object of this study is the quarterly financial report of PT. Bank Muamalat Indonesia for the period 2018-2022. The data collection technique uses documentation with multiple linear regression analysis tests. The results of the t-test analysis show that partially the DPK variable has no effect on financing with a significance value of 0.100> 0.05 and a t-count value of 1.748 <t table 2.120. The NPF variable does not affect financing because the significance value is 0.308> 0.05 with a t-count value of 1.054 <2.120. The CAR variable affects financing with a significance value of 0.00 <0.05 and a t-count value of 7.131> 2.120. Simultaneously, the DPK, CAR, and NPF variables affect financing. This is proven by the sig-F value of 0.00 < 0.05 and the comparison of F table (3.20) < F count (21,773). The predictive ability of the three variables on financing is 76.6% as indicated by the amount of adjusted R2, while the remaining 23.4% is influenced by other ratio factors.